Reproductive Health Matters among Indian Adolescents: A Qualitative Study - Asha Hegde; Avinash Shetty; Veena Kamath; Unnikrishnan Bhaskaran; Asha Kamath; Kallol Roy; Lena Ashok; Mamatha Laxminarayan (Mashhad University of Medical Sciences, 2017)
Background & aim: Qualitative perspectives of the reproductive health (RH) facilities and Adolescent Friendly Health Services (AFHS) are still unexplored issues among the Indian adolescents. Regarding this, the aim of the present study was to explore the perceptions and awareness about the RH and its facilities among the adolescents in two districts in India. Methods: This qualitative study was conducted on 197 individuals (i.e., 102 boys and 95 girls within the age of 15-19 years), selected from two Indian districts through stratified purposeful sampling method. For the purpose of the study, 16 focus group discussions (FGD) were held using pre-tested FGD guide. All tape-recorded data were fully transcribed and thematic analysis was performed using inductive coding. Results: As the results indicated, a set of four themes, 12 subthemes, 52 open codes, and 12 categories was developed. The boys had lower parent-child proximity for discussing puberty changes, compared to the girls. They were totally unaware of the state sponsored RH services. On the other hand, the girls had better access to health care schemes provided by the government. Conclusion: According to the findings,the utilization of the RH services was poor among the adolescents in the two districts investigated in this study. It would be advisable to carry out more studies addressing the RH-related concerns of the adolescents, especially the boys.